Sustainable development in the Arab world – is the Gulf Cooperation Council (GCC) region fit for the challenge? - Esmat Zaidan (16855203) (2019)
The Gulf Cooperation Council (GCC) region and the wider Arab world are faced with multiple inter-connected dilemmas embedded in the social, economic, and environmental pillars of sustainable development. The question of how to design effective sustainability strategies that are alignedwith the context of the GCC region is a relevant one. In this special issue, contributors have investi-gated the obstacles to sustainable development in the GCC region, the impact of current develop-ment patterns on the sustainability agenda, and the way in which countries react to local,regional, and global sustainability pressures and debates. The issue aimed to provide a platformfor academics to present policy-relevant research and practical steps being taken towards realisinggenuine sustainable development within the GCC region, while teasing out the major obstacles tothis process. This regional focus is motivated by the shared challenge of GCC countries of reformingcarbon-based economies as well as their systems of high subsidisation and universal benefits in orderto incorporate sustainable concerns, merit-based rules, and more targeted policies. While these chal-lenges are shared with other Arab countries, as well as other countries exporting oil and gas, theorigins, current patterns, and future directions of sustainability reforms in the GCC region reveal inter-esting lessons to be learnt. Other Information Published in: Development in Practice License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/09614524.2019.1628922